GENERAL-PURPOSE INNOVATION RESULTS MONITORING - V. V. Krasnoproshin; A. I. Kuzmich; A. N. Valvachev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
There is a technique offered that enables to objectively evaluate the impact of the innovation results on the business processes, the environment condition and public health, and to synthesize a proper managing decision. A scenario of using the said technique for a certain applied task has been devised with the resultant solution presented.